Climate change and agriculture: A Nepalese case - Rai, Mandip (Journal of Agriculture and Environment, 2007)
Despite having slight disagreements on the magnitude, timing and spatial distribution of climate change, scientists agree that the recent climate change has been much faster than in the past. This has been partly to the natural phenomenon but mostly because of human activities. There is also an agreement that the poorer nations will suffer more as a consequence of the climate change than the developed nations. In this connection, the Nepalese agriculture does not seem to gain but rather lose during the process of global climate change. Even so, serious preparedness and actions can be taken that can hopefully impede the process of climate change and slowly but surely adapt to the rapidly changing climate. To achieve that, agriculture’s role as a driving force for climate change can be condensed by taking measures that reduce the rate and volume of Greenhouse Gas emissions from agriculture on the one hand, and developing diverse and resilient plant and animals breeds, on the other, that are capable of yielding as much as the current levels or even better under the foreseen changed climatic conditions. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 92-95